Memória e estranhamento em poemas, traduções e ensaios de José Paulo Paes - Paulo Roberto Barreto Caetano (2015)
This research aims to discuss the relationship between memory and strangeness in José Paulo Paes' poems, translations and essays. To investigate this possibility, the thesis focuses on three books by the writer of São Paulo:'Prosas seguidas de Odes mínimas', 'Poesia erótica em tradução' and 'O lugar do outro'. The first book consists of poems by Paes (in which can be seen, for example, a desire to poeticise trivial things, removing this from an ordinary place). In the first chapter of the thesis, in the light of 'O estranho', by Freud, it is discussed how Paes' poems deals with the everyday life. It is also studied in the light of Philippe Lejeune how the biographical and poetic discourses interact with each other, making a familiar poetic metaphor. The second chapter, in turn, has as an object of research, the collection of erotic poems selected and translated by José Paulo (in which can be seen a desire to maintain aspects of the source texts, as well as an intention to work with an unconventional theme, according to the author). From Schleiermacher, the chapter discusses this desire to foreignize the act of translation. To accomplish this, the chapter made use of the 'Nota liminar' written by Paes in the book in question, as well as the book 'Tradução: a ponte necessária'. 'Aspectos e problemas da arte de traduzir', in which the writer makes a critical and theoretical exercise of translation, that allowed reflections about some of his translational choices. Finally, the third chapter, focuses on the book of essays, in which texts were published in national newspapers. 'O lugar do outro' is a publication of texts that perceive, for example, the novel as a place for the excellence of otherness, and reflect on the measured use of language as a mechanism to prevent weariness from itself. With such diversity, the research seeks to work with the essay as a text opened to attriction, as Silvina Rodrigues higlighted, to think not only about the issue of language in the paper and its critical potential, which is not only restricted to literature, observing the surroundings and discussing what would be (potentially) strange. This contact with the strangeness, the idea of search made by the memory is recurrently observed, which was analyzed by Ricoeur: an active memory, which provides the establishment for different discourses. Through this focus, the thesis approaches different José Paulo's texts, discussing a thread that goes through.